Reliability and Agreement of Hand-Held Dynamometry Using Three Standard Rater Test Positions - Frank Aerts; Holly Sheets; Chance Anderson; Natalie Bussie; Rose Hoskins; Amanda Maninga; Emily Novak (International Journal of Sports Physical Therapy)
# Background